‘Making Ground’: An Ethnography of ‘Living With’ Harmful Methamphetamine Use and the Plurality of Recovery - Brookfield, Samuel (Journal of drug issues, 2022)
The trajectories of people attempting to reduce harmful methamphetamine use are frequently understood within a binary framework of transitioning between states of health and disease. This framework can often be reinforced by service interactions informed by these dominant narratives of recovery and addiction. In this paper, we draw on a critical interactionist analysis of ethnographic fieldwork conducted with people who use methamphetamine, to examine how their experiences could undermine this binary, observing the ways participants experienced growth, change, and progress, without necessarily maintaining abstinence. These findings support a more diverse understanding of drug use trajectories, and we explore the concept of ‘living with drug use’, similar to how people live with other chronic conditions by finding ‘health in illness’. Participant experiences are also interpreted within the context of counter public health, arguing for the recognition and integration of values and goals which are divergent from the implicit aims of public health practice.